Ülkemiz müzik eğitiminde klasik gitar - Halvaşi, A. Aylin (My University, 1999)
The research titled Classical Guitar in the Musical Education of Our Country focuses on the place of the classical guitar in the musical education and its contribution. Musical education is the procedure of helping the individual to gain musical behaviors purposefully through his own experiences or to change his musical behaviors again purposefully through his own experiences. It is a branch of artistic education. Although musical education, divided into three main categories, namely general, amateur and vocational, is considered as a whole in the research, the current position of the classical guitar particularly from the instrumental training perspective of these categories is defined and some recommendations are put forward on the development of its practical aspect. It is obvious that there is an enormous interest and love (appreciation) in classical guitar in Turkey. It is evident that the instrument has many advantages due to its characteristics such as its use as a solo instrument as well as an accompanying one, its convenience for polyphony and carriage, and its affordability. The data gathered by a survey on the general musical education conducted among the music teachers and students in primary and secondary schools, proved that classical guitar was not sufficiently used in musical education. Recommendations are given on the instrument, declared to be conveniently used in the classroom as well as an accompaniment instrument, to encourage its prevalence and use for the activities inside and outside the classroom. It is recognized that the training provided with respect to amateur musical education meets the need in the field to a certain extent. However, it is perceived that the amateur instrument education varies in teachers and institutions providing the training concerned. Thus it is stated that the education given shall be standardized. It is also recommended that the number of people and institutions providing the training shall be increased in accordance with the subjects concerned. It is mentioned that the institutions providing the vocational musical education shall be improved with respect to number, program, program development studies and physical properties. The significance of the educational institutions for music teachers to have classical guitar courses and repertoire studies for the musical education in schools is also declared. It is clearly stated that the conservatories and universities where guitar virtuosos and teachers are trained, have a significant role in encouraging the prevalence of the instrument properly. Consequently, recommendations are created on the most beneficial use of the classical guitar, on the basis of general, amateur and vocational categories, in the educational music of the future with respect to the instrumental training of the musical education which provides the individual to have more conscious, healthy, proper and efficient communication and interaction with others. The survey and interview techniques used in the field for the people involved, are in the core of the above mentioned recommendations.

Ülkemiz Müzik Eğitiminde Klasik Gitar konulu araştırmada klasik gitarın müzik eğitimindeki yeri ve sağlayacağı katkılar üzerinde durulmuştur. Müzik eğitimi, bireye kendi yaşantıları yoluyla, amaçlı olarak müziksel davranışlar kazandırma, ya da bireyin müziksel davranışlarını kendi yaşantıları yoluyla amaçlı olarak değiştirme sürecidir. Sanat eğitiminin bir koludur. Araştırmada müzik eğitimi bir bütün olmakla birlikte, genel, amatör ve mesleki olmak üzere üç ana grupta incelenmiş, özellikle bu grupların çalgı eğitimi boyutunda klasik gitarın mevcut yeri tespit edilerek, kullanım alanının geliştirilmesine yönelik öneriler ortaya atılmıştır. Ülkemizde klasik gitara karşı büyük bir ilgi ve sevgi duyulduğu kesinlik kazanmıştır. Çalgının gerek solo gerek eşlik çalgısı olarak kullanılabilirliği, çok sesliliğe yatkınlığı, kolay taşınabilirliği, diğer çalgılara göre maddi açıdan daha kolay temin edilebilirliği vb özellikleri ile büyük avantajlar taşıdığı anlaşılmıştır. Genel müzik eğitimi doğrultusunda ilköğretim ve ortaöğretim kurumlarında müzik dersi veren öğretmen ve bu dersi alan öğrencilere yapılan anketten elde edilen bulgular, okul müzik eğitiminde klasik gitardan yeteri kadar yararlanılmadığını ortaya çıkartmıştır. Bu alanda gerek sınıf gerek eşlik çalgısı olarak kullanım imkanı sağladığı kabul edilen çalgının yaygınlaştırılması, ders içi ve ders dışı faaliyetlerde kullanılmasına yönelik öneriler oluşturulmuştur. Amatör müzik eğitimi açısından gerçekleştirilen eğitimin bu alandaki ihtiyacı karşılamaya destek verdiği ortaya çıkmıştır. Ancak amatör çalgı eğitiminin, eğitimi veren kişi ve kuruluşlarda farklılıklar gösterdiği anlaşılmış bu yönden gerçekleştirilmeye çalışılan eğitimin, belli bir standarda kavuşturulması gerekliliği ifade edilmiştir. Bu alanda eğitim veren kişi ve kuruluşlarında ifade edilen konular doğrultusunda yaygınlaştırılması önerilmiştir. Mesleki müzik eğitimi açısından bu alanda eğitim veren kurumların sayı, program, program geliştirme çalıştırmaları ve fiziksel özellikler bakımından geliştirilmesi gerektiği üzerinde durulmuştur. Özellikle müzik öğretmeni yetiştiren kurumların ders programlarında klasik gitara yer verilmesinin ve okul müzik eğitimine yönelik repertuar çalışmalarının yapılmasının önemi ortaya konulmuştur. Gitarist ve gitar eğitimcisi yetiştiren konservatuarların ve lisans üstü eğitim veren kurumların, çalgının düzeyli bir şekilde yaygınlaştırılmasındaki önemi daha net belirtilmiştir. Her üç grupta da klasik gitar eğitiminin geliştirilmesi ve yaygınlaştırılmasında kitap, metot, dergi, CD, radyo ve televizyon yayınlarının önemi ve çalgı temini probleminin çözümü üzerinde durulmuştur. Sonuç olarak bireyin çevresi ile daha bilinçli, daha sağlıklı, daha düzenli, daha verimli bir iletişim ve etkileşim sağlamasını sağlayan müzik eğitiminin çalgı eğitimi boyutunda, klasik gitarın genel, amatör ve mesleki açıdan ileriye dönük şekilde, eğitim müziğinde en yararlı biçimde nasıl kullanılabileceğine yönelik öneriler oluşturulmuştur. Bu alanda ilgili kişilere yapılan anket ve görüşme teknikleri bu önerilerin kaynağında ağırlık kazanmıştır.
Keywords: araştırma; Eğitim; gösteriler; ilgili konular; KLASİK GİTAR; Müzik; MÜZİK EĞİTİMİ